Design of an interactive tool for Evokube - Chua, Benny Wei Liang (2019)
Developing an interactive tool for a new construction play toy called Evokube designed and invented by PABensen Pte. Ltd. involves user interface design, 3D modelling and software development. This report will cover the design process of the interactive tool, from researching fundamental concepts behind the Graphical User Interface (GUI) design to actual design implementation. The mechanics of how users can use the Evokube interactive tool to create 3D models virtually will also be explained. Adobe Photoshop CC was used to design the GUI such that it is aesthetically pleasing and intuitive for users to use it, and simultaneously making the design as user-friendly as possible. Animation and audio were also incorporated into the interactive tool using Unity.